Nutritional status and measles antibody titer in children living in urban slums of Mumbai - Huey, Samantha; Russell, David; Haas, Jere D.; Venkatramanan, Sudha; Finkelstein, Julia L.; Mehta, Saurabh (American Society for Nutrition, 2020)
To determine a) the prevalence of protective measles IgG titers in young children living in urban slums of Mumbai, and b) the association of nutritional status assessed through a combination of anthropometry and micronutrient biomarker concentrations with these titers at baseline and after 9 months of follow-up.